Time-varying parameters in monetary policy rules - Anderl, Christina,Caporale, Guglielmo Maria (CESifo, 2023)
This paper assesses time variation in monetary policy rules by applying a Time-Varying Parameter Generalised Methods of Moments (TVP-GMM) framework. Using monthly data until December 2022 for five inflation targeting countries (the UK, Canada, Australia, New Zealand, Sweden) and five countries with alternative monetary regimes (the US, Japan, Denmark, the Euro Area, Switzerland), we find that monetary policy has become more averse to inflation and more responsive to the output gap in both sets of countries over time. In particular, there has been a clear shift in inflation targeting countries towards a more hawkish stance on inflation since the adoption of this regime and a greater response to both inflation and the output gap in most countries after the global financial crisis, which indicates a stronger reliance on monetary rules to stabilise the economy in recent years. It also appears that inflation targeting countries pay greater attention to the exchange rate pass-through channel when setting interest rates. Finally, monetary surprises do not seem to be an important determinant of the evolution over time of the Taylor rule parameters, which suggests a high degree of monetary policy transparency in the countries under examination.
10419/279200
Keywords: Graue Literatur; Taylor rules; monetary policy rules; Generalised Methods of Moments; Time-varying parameters